2004
DOI: 10.1021/jp0482114
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of the Vapor−Liquid−Liquid Phase Behavior in Ternary Mixtures Consisting of n-Alkanes, n-Perfluoroalkanes, and Carbon Dioxide

Abstract: Expansion of an organic solvent by an inert gas can be used to tune the solvent's liquid density, solubility strength, and transport properties. In particular, gas expansion can be used to induce miscibility at low temperatures for solvent combinations that are biphasic at standard pressure. Configurational-bias Monte Carlo simulations in the Gibbs ensemble were carried out to investigate the vapor-liquid-liquid equilibria and microscopic structures for two ternary systems: n-decane/n-perfluorohexane/CO2 and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…This reduction in the H−F atom interactions is comparable to a reduction of 10% in united atom models. Zhang and Siepmann, 12 using the united atom version of the TraPPE force field, found that a 1% increase of the unlike size parameter and an 11% reduction of the unlike well depth were necessary to obtain an adequate fit of the liquid−liquid envelope for the CH 4 /CF 4 mixture. More recently, Potoff and Bernard-Brunel 13 developed united atom force fields for alkanes and perfluoroalkanes based on Mie potentials.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in the H−F atom interactions is comparable to a reduction of 10% in united atom models. Zhang and Siepmann, 12 using the united atom version of the TraPPE force field, found that a 1% increase of the unlike size parameter and an 11% reduction of the unlike well depth were necessary to obtain an adequate fit of the liquid−liquid envelope for the CH 4 /CF 4 mixture. More recently, Potoff and Bernard-Brunel 13 developed united atom force fields for alkanes and perfluoroalkanes based on Mie potentials.…”
Section: Introductionmentioning
confidence: 99%
“…at many mole fractions to give an accurate result, and therefore be very time-consuming. Instead, we determine activity coefficients by fitting the parameters in the (appropriately differentiated) modified Margules [4] equation for G E , 12 α 21 x 1 x 2 α 12 x 1 + α 21 x 2 + ηx 1 x 2 (1.3) to the simulation results from Eq. (1.2).…”
Section: Fluctuation Solution Theory Methodologymentioning
confidence: 99%
“…Our atomic charges are the same as those of Chen et al [8] except for the carbon atoms attached to fluorines. In the united atom force fields available for fluoroalkanes [11,12], the CF 2 and CF 3 beads are electro-neutral. We retained this feature by making the corresponding groups of atoms electro-neutral in the HFF-227ea description.…”
Section: Force Field Parametersmentioning
confidence: 99%
“…Mixtures of CO 2 and n-alkanes have been studied extensively both by experiment (71)(72)(73)(74)(75)(76)(77)(78) and more recently through Monte Carlo simulations (34,47,(79)(80)(81)(82). In Fig.…”
Section: Binary Constituentsmentioning
confidence: 99%